Characteristics of Earthquake-Generated Tsunamis in Indonesia Based on Source Parameter Analysis - Sugeng Pribadi; A. Afnimar; Nanang T. Puspito; Gunawan Ibrahim (Institute for Research and Community Services (LPPM) ITB, 2013)
We have characterized 27 earthquake-generated tsunamis from 1991 to 2012 in Indonesia, based on source parameter analysis. This includes the focal mechanism derived by W phase inversion analysis, the ratio (Θ) between the seismic energy (E) and the seismic moment (Mo), the moment magnitude (Mw), the rupture duration (To) and the distance of the hypocenter to the trench. Most of the earthquakes (24 events) were tsunamigenic earthquakes with various fault types, a shallow focal depth (12 km ≤ D ≤ 77.8 km), a small to large magnitude (6.6 ≤ Mw ≤ 9.0), a low ratio of seismic energy to seismic moment (-5.8 < Θ < -4.9), a short to long rupture duration (27 s ≤ To ≤ 257 s), a small to large tsunami height (0.1 m ≤ H ≤ 50.9 m) and a short to long distance from the hypocenter to the trench (10 km < HT ≤ 230 km). Three tsunami earthquakes were characterized by a thrust fault mechanism, a very shallow depth (D ≤ 20 km), a moderate magnitude (7.5 ≤ Mw ≤ 7.8), a very low ratio of seismic energy to seismic moment (Θ ≤ -5.8), a long rupture duration (99 s ≤ To ≤ 135 s), a large tsunami height (7.4 m ≤ H ≤ 14 m) and a short distance from the hypocenter to the trench (HT ≤ 20 km).